Responding to "change" in the sporting environment: A brief review of recent agility testing and training research - Holding, R. C.; Meir, R. A.; Zhou, S. (Journal of Australian Strength and Conditioning, 2013)
The ability to display high levels of speed whilst changing direction is of vital importance for athletes competing in open-type sports such as soccer, football, field hockey, rugby, etc. Recently in the literature, researchers have highlighted that in the performance setting, athletes are repeatedly challenged to display fast and efficient movement in response to stimuli within the environment. As a result, the definition of agility has been updated from describing simple change-of-direction movements to incorporating both a physical movement and a perceptual decision-making component. This has given rise to research into differing strategies in relation to testing and training for agility performance that challenges both the athlete's physical movement and their perceptual and decision making ability. The purpose of this brief review is to highlight the recent literature regarding the development of sport specific agility testing and training protocols. Recent publications with a focus on producing new tests of agility and also studies that have attempted to promote agility by developing both the athlete`s movement ability and perceptual-cognitive ability have been reviewed. Considerations for coaches including the inclusion of agility drills that challenge the athlete`s perceptual abilities are highlighted.